Preparation method of wave absorbing material, wave absorbing material and application thereof

By combining Ti3C2Tx and carbonyl iron powder with aramid paper honeycombs, an absorbing material with good absorbing performance at a smaller honeycomb height was prepared, which solved the problem of insufficient absorbing performance of existing honeycomb structure stealth materials and achieved a more efficient electromagnetic wave absorption effect.

CN119774653APending Publication Date: 2025-04-08SHENZHEN SUNWAY COMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411871284.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing cellular structure stealth materials still have room for improvement in wave absorption performance, especially when it is difficult to achieve better wave absorption effect at smaller cellular heights.

Method used

The absorbing slurry is prepared by mixing Ti3C2Tx, carbonyl iron powder, polymer adhesive and organic solvent, and coated on the surface of the aramid paper honeycomb and then dried to form an absorbing material with a honeycomb structure. Through the synergistic action of Ti3C2Tx and carbonyl iron fine powder, this material improves electromagnetic wave absorption performance by utilizing mechanisms such as conductive loss, multiple reflection and magnetic loss.

Benefits of technology

At a smaller honeycomb height, the prepared wave absorbing material significantly improves the electromagnetic wave absorption performance and achieves better wave absorbing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774653A_ABST
    Figure CN119774653A_ABST
Patent Text Reader

Abstract

The embodiments of the present application relate to the field of wave absorbing material technology, and in particular to a method for preparing a wave absorbing material, a wave absorbing material and its application. In the embodiments of the present application, the wave absorbing slurry includes Ti3C2T x and carbonyl iron powder; therefore, the absorbing slurry is coated on the surface of the aramid paper honeycomb, and the absorbing material obtained after drying includes the aramid paper honeycomb and the absorbing coating covering the surface of the aramid paper honeycomb, and the absorbing coating includes Ti3C2T x and carbonyl iron powder, among which Ti3C2T x It has high electrical conductivity, special morphological structure and adjustable surface functional groups, and can attenuate electromagnetic waves through conductive loss, multiple reflections, polarization loss, etc. Carbonyl iron powder has good low-frequency wave absorption performance and multiple loss mechanisms, which can further improve the wave absorption performance of the absorbing material. x The synergistic effect between carbonyl iron powder and aramid paper honeycomb can effectively improve the absorbing performance of honeycomb structure absorbing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of absorbing materials, and in particular to a method for preparing absorbing materials, absorbing materials and applications thereof. Background Art

[0002] According to the molding process and load-bearing capacity, absorbing materials can be divided into two categories: coating absorbing materials and structural absorbing materials. Structural absorbing materials have the dual functions of bearing and reducing radar cross-section. They can reduce structural mass, increase effective load, greatly reduce costs, and have been widely used.

[0003] Honeycomb structure stealth material is one of the commonly used structural stealth materials; it can not only bear as a structural component, but also absorb electromagnetic waves well, and has become an important development direction of contemporary stealth materials. However, with the rapid development of science and technology, the requirements for the wave absorption performance of honeycomb structure stealth materials are increasing, and the wave absorption performance of existing honeycomb structure stealth materials needs to be improved. Summary of the invention

[0004] In order to further improve the wave-absorbing performance of the honeycomb structure stealth material, the embodiments of the present application provide a method for preparing a wave-absorbing material, a wave-absorbing material and its application, which can enable the wave-absorbing material to obtain better wave-absorbing performance at a smaller honeycomb height.

[0005] In a first aspect of the present application, a method for preparing an absorbing material is provided, the method comprising: x , carbonyl iron powder, polymer adhesive and organic solvent are mixed to obtain a microwave absorbing slurry; the microwave absorbing slurry is coated on the surface of the aramid paper honeycomb; the aramid paper honeycomb coated with the microwave absorbing slurry is dried to obtain a microwave absorbing material with a honeycomb structure.

[0006] In the embodiment of the present application, the absorbing slurry includes Ti3C2T x , carbonyl iron powder and polymer adhesive; therefore, the absorbing slurry is coated on the surface of the aramid paper honeycomb, and the absorbing material obtained after drying includes the aramid paper honeycomb and the absorbing coating covering the surface of the aramid paper honeycomb, and the absorbing coating includes Ti3C2T x and carbonyl iron powder, among which Ti3C2T x It has high electrical conductivity, special morphological structure and adjustable surface functional groups, and can attenuate electromagnetic waves through conductive loss, multiple reflections, polarization loss and other means. Carbonyl iron powder has good low-frequency wave absorption performance and multiple loss mechanisms, which can further improve the wave absorption performance of absorbing materials. The honeycomb structure of aramid paper honeycomb can further absorb electromagnetic waves through multiple reflection losses. xUsed in combination with carbonyl iron powder, Ti3C2T x The synergistic effect between carbonyl iron powder and aramid paper honeycomb can effectively improve the absorbing performance of honeycomb structure absorbing materials.

[0007] In some embodiments, the Ti3C2T x The mass ratio of the carbonyl iron powder to the carbonyl iron powder is in the range of (1:3) to (1:1).

[0008] In some embodiments, the carbonyl iron powder and the Ti3C2T x The mass ratio of the total mass of the adhesive to the polymer adhesive is 5:1.

[0009] In some embodiments, the polymer adhesive is acrylic resin or polyurethane resin.

[0010] In some embodiments, coating the absorbing slurry on the surface of the aramid paper honeycomb comprises: coating the absorbing slurry on the surface of the aramid paper honeycomb by an impregnation method.

[0011] In some embodiments, the polymer adhesive is an acrylic resin, the organic solvent is butanone and cyclohexanone; x , carbonyl iron powder, polymer adhesive and organic solvent are mixed to obtain a microwave absorbing slurry, comprising: mixing 10 g of acrylic resin, 20 mL of butanone and 80 mL of cyclohexanone to obtain a first mixture; mixing the first mixture with 1.5 g of carbonyl iron powder and 0.5 g of Ti3C2T x Mix to obtain a microwave absorbing slurry.

[0012] In some embodiments, the polymer adhesive is a polyurethane resin, the organic solvent is dimethyl sulfoxide and xylene; x , carbonyl iron powder, polymer adhesive and organic solvent are mixed to obtain a microwave absorbing slurry, comprising: mixing 10 g of polyurethane resin, 70 mL of dimethyl sulfoxide and 30 mL of xylene to obtain a second mixture; mixing the second mixture, 1.0 g of carbonyl iron powder and 1.0 g of Ti3C2T x Mix to obtain a microwave absorbing slurry.

[0013] In some embodiments, the absorbing material includes the aramid paper honeycomb and an absorbing coating disposed on the surface of the aramid paper honeycomb, the absorbing coating is obtained by drying the absorbing slurry, and the thickness of the absorbing coating ranges from 1.85 mm to 2.00 mm.

[0014] In the second aspect of the present application, a wave absorbing material is further provided. The wave absorbing material is prepared according to the method described in the first aspect.

[0015] In the third aspect of the present application, there is also provided an application of an absorbing material prepared by the method described in the first aspect in the field of electromagnetic wave absorption.

[0016] It should be understood that the contents described in the summary of the invention are not intended to limit the key or important features of the present disclosure, nor are they intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 is a schematic flow chart of a method for preparing an absorbing material provided in some embodiments of the present application;

[0019] Figure 2 It is a schematic diagram of the partial structure of aramid paper honeycomb provided in some embodiments of the present application. DETAILED DESCRIPTION

[0020] The principles and spirit of the present disclosure will be described below with reference to several exemplary embodiments shown in the accompanying drawings. It should be understood that the description of these specific embodiments is only to enable those skilled in the art to better understand and implement the present disclosure, and does not limit the scope of the present disclosure in any way. In the following description and claims, unless otherwise defined, all technical and scientific terms used herein have the meanings commonly understood by those of ordinary skill in the art.

[0021] As used herein, the term "including" and similar terms should be understood as open inclusion, i.e., "including but not limited to". The term "based on" should be understood as "based at least in part on". The term "one embodiment" or "the embodiment" should be understood as "at least one embodiment". The terms "first", "second", etc. may refer to different or the same objects, and are only used to distinguish the objects referred to, without implying a specific spatial order, temporal order, order of importance, etc. of the objects referred to.

[0022] See also Figure 1 , Figure 1 The process of preparing the wave absorbing material provided by one embodiment of the present application is shown. Figure 1 As shown, the method comprises the following steps:

[0023] Step 11: Ti3C2T xThe microwave absorbing slurry is obtained by mixing carbonyl iron powder, polymer adhesive and organic solvent.

[0024] Ti3C2T in the embodiment of the present application x MXene materials. MXene materials are a class of metal carbon / nitrides with a two-dimensional layered structure, and their general chemical formula is M n+1 X n T x , where (n = 1-3), M represents an early transition metal, such as Ti, Zr, V, Mo, etc.; X represents C or N elements, T x It is a surface group, usually -OH, -O, -F or -Cl. It is named MXene because it has a sheet structure similar to graphene. x It has the characteristics of high electrical conductivity, special morphological structure and controllable surface functional groups, which enables it to attenuate electromagnetic waves through conductive loss, multiple reflections, polarization loss and other means.

[0025] In some embodiments, carbonyl iron, i.e., metallic iron, reacts with CO to generate gaseous hydroxy iron, which is then decomposed to generate metallic iron powder. The particle size of hydroxy iron micropowder is generally 0.5 μm-20 μm. The loss mechanism of hydroxy iron micropowder is mainly ferromagnetic resonance absorption, which has a large loss angle. Hydroxy iron micropowder attenuates and absorbs radar waves by eddy current loss, hysteresis loss, and residual loss mechanisms. Hydroxy iron micropowder has both free electron absorption and magnetic loss, and theoretically has better absorption performance than ferrite.

[0026] In some embodiments, the polymer adhesive can be any suitable polymer resin. Specifically, when the polymer adhesive is acrylic resin or polyurethane resin, the bonding strength between the radar absorbing coating and the aramid paper honeycomb is higher.

[0027] In some embodiments, the organic solvent may be any suitable organic solvent that can dissolve the polymer adhesive. In some embodiments, the organic solvent may be at least one of butanone, cyclohexanone, dimethyl sulfoxide, and xylene. For example, when the polymer adhesive is an acrylic resin, the organic solvent may be butanone and cyclohexanone, and the volume ratio of butanone to cyclohexanone may be 1:4; when the polymer adhesive is a polyurethane resin, the organic solvent may be dimethyl sulfoxide and xylene, and the volume ratio of dimethyl sulfoxide to xylene may be 7:3.

[0028] In the embodiments of the present application, Ti3C2T xAfter the carbonyl iron powder, polymer adhesive and organic solvent are evenly mixed, the microwave absorbing slurry is obtained. Specifically, the polymer adhesive and organic solvent can be added into a container, and the mixture in the container is stirred at 80°C-90°C, wherein the stirring time is 1.5h-2.5h, and the stirring speed is 300r / min-400r / min; after the mixture in the container is cooled, Ti3C2T x and carbonyl iron powder, and then stirring the mixture in the container to obtain a microwave absorbing slurry after stirring evenly.

[0029] In some embodiments, in order to further improve the absorbing performance of the absorbing material, Ti3C2T x The mass ratio of Ti3C2T to carbonyl iron powder is in the range of (1:3) to (1:1). x A mass ratio of carbonyl iron powder to carbonyl iron powder less than 1:3 or greater than 1:1 is not conducive to improving the absorbing performance of the absorbing material.

[0030] In some embodiments, in order to further improve the absorbing performance of the absorbing material, carbonyl iron powder and Ti3C2T x The total mass ratio of carbonyl iron powder and Ti3C2T x When the ratio of the total mass of the absorbent to the mass of the polymer adhesive is 5:1, the absorbing performance of the absorbing material is the best.

[0031] In some embodiments, in order to further improve the absorbing performance of the absorbing material, step 11 specifically includes: mixing 10 g of acrylic resin, 20 mL of butanone and 80 mL of cyclohexanone to obtain a first mixture; mixing the first mixture with 1.5 g of carbonyl iron powder and 0.5 g of Ti3C2T x Mix to obtain a microwave absorbing slurry.

[0032] In other embodiments, in order to further improve the absorbing performance of the absorbing material, step 11 specifically includes: mixing 10 g of polyurethane resin, 70 mL of dimethyl sulfoxide and 30 mL of xylene to obtain a second mixture; mixing the second mixture, 1.0 g of carbonyl iron powder and 1.0 g of Ti3C2T x Mix to obtain a microwave absorbing slurry.

[0033] Step 12: Apply the microwave absorbing slurry to the surface of the aramid paper honeycomb.

[0034] Step 13: Drying the aramid paper honeycomb coated with the microwave absorbing slurry to obtain a microwave absorbing material with a honeycomb structure.

[0035] In the embodiments of the present application, aramid paper honeycomb is a honeycomb core material made of aramid paper as the main raw material. Its structure and appearance are similar to the cells of a honeycomb, and it is a hexagonal honeycomb structure that imitates a natural honeycomb. Compared with honeycomb cores made of other materials, aramid paper honeycomb has better compatibility with various resin systems; at the same time, aramid paper honeycomb has high strength, high stiffness, low density, excellent insulation performance and good chemical inertness. For example, Figure 2 The schematic diagram of the structure of the aramid paper honeycomb is shown. The aramid paper is enclosed into several regular polygons, and the side length of each regular polygon is L. The height of the aramid paper honeycomb is D.

[0036] In some embodiments, step 12 specifically includes: applying the absorbing slurry to the surface of the aramid paper honeycomb by an impregnation method. Specifically, the aramid paper honeycomb has a plurality of through holes with a regular hexagonal cross section. The aramid paper honeycomb on one side of the through hole can be vertically placed in the absorbing slurry, and immersed for a certain time (such as 1 minute), and then dried to remove the solvent in the absorbing slurry; then, the aramid paper honeycomb on the other side of the through hole is vertically placed in the absorbing slurry, and immersed for a certain time (such as 1 minute), and then dried to obtain the absorbing material.

[0037] In the embodiments of the present application, the absorbing slurry coated on the aramid paper honeycomb forms an absorbing coating after drying. Therefore, the absorbing material includes the aramid paper honeycomb and the absorbing coating covering the surface of the aramid paper honeycomb. In some embodiments, when the thickness of the absorbing coating ranges from 1.85 mm to 2.00 mm, the absorbing performance of the absorbing material is the best.

[0038] The embodiment of the present application also provides an absorbing material, which is prepared according to the method provided in the above embodiment.

[0039] The embodiments of the present application also provide an application of an absorbing material prepared by the method provided in the above embodiments in the field of electromagnetic wave absorption.

[0040] In the embodiment of the present application, the absorbing slurry includes Ti3C2T x , carbonyl iron powder and polymer adhesive; therefore, the absorbing slurry is coated on the surface of the aramid paper honeycomb, and the absorbing material obtained after drying includes the aramid paper honeycomb and the absorbing coating covering the surface of the aramid paper honeycomb, and the absorbing coating includes Ti3C2T x and carbonyl iron powder, among which Ti3C2T xIt has high electrical conductivity, special morphological structure and adjustable surface functional groups, and can attenuate electromagnetic waves through conductive loss, multiple reflections, polarization loss and other means. Carbonyl iron powder has good low-frequency wave absorption performance and multiple loss mechanisms, which can further improve the wave absorption performance of absorbing materials. The honeycomb structure of aramid paper honeycomb can further absorb electromagnetic waves through multiple reflection losses. x Used in combination with carbonyl iron powder, Ti3C2T x The synergistic effect between carbonyl iron powder and aramid paper honeycomb can effectively improve the absorbing performance of honeycomb structure absorbing materials.

[0041] Several embodiments of the present application are provided below.

[0042] Example 1

[0043] 10g of acrylic resin was added to the first container containing 20mL of butanone and 80mL of cyclohexanone. The mixture in the first container was stirred for 2h at 80°C with a stirrer at a speed of 350r / min. After the mixture in the first container was cooled naturally, 1.5g of carbonyl iron powder and 0.5g of Ti3C2T x powder, and then fully stir the mixture in the first container to obtain a microwave absorbing slurry after stirring evenly.

[0044] The end of the aramid paper honeycomb close to the first surface is vertically placed in the absorbing slurry for 1 minute, then taken out vertically, and after being fully dried at 60°C, the aramid paper honeycomb is horizontally turned over, and the end of the aramid paper honeycomb close to the second surface is immersed in the absorbing slurry for 1 minute. After drying, the absorbing material is obtained, wherein the first surface and the second surface are arranged opposite to each other.

[0045] Example 2

[0046] 10g of polyurethane resin was added to a second container containing 70mL of dimethyl sulfoxide and 30mL of xylene. The mixture in the second container was stirred at 90°C for 2h with a stirrer at a speed of 350r / min. After the mixture in the second container was cooled naturally, 1.0g of carbonyl iron powder and 1.0g of Ti3C2T x The mixture in the second container is fully stirred to obtain a microwave absorbing slurry after being stirred evenly.

[0047] The end of the aramid paper honeycomb close to the first surface is vertically placed in the absorbing slurry for 1 minute, then taken out vertically, and after being fully dried at 60°C, the aramid paper honeycomb is horizontally turned over, and the end of the aramid paper honeycomb close to the second surface is immersed in the absorbing slurry for 1 minute. After drying, the absorbing material is obtained, wherein the first surface and the second surface are arranged opposite to each other.

[0048] In Example 1 and Example 2, the side length L of each regular polygon enclosed by the aramid paper is 2.75 mm. The length and width of the aramid paper honeycomb are both 300 mm. The height D of the aramid paper honeycomb is 20 mm.

[0049] The method for preparing the absorbing material provided in the embodiment of the present application uses Ti3C2T x The conductive loss and magnetic loss of the carbonyl iron powder and the synergistic effect of the honeycomb structure make the prepared absorbing material have a good electromagnetic wave absorption effect. Among them, the absorbing material provided in Example 1 has a maximum electromagnetic wave absorption intensity of -62.5dB when the thickness of the absorbing coating is 1.85mm; the absorbing material provided in Example 2 has a maximum electromagnetic wave absorption intensity of -65.2dB when the thickness of the absorbing coating is 2.00.

[0050] The type of absorbing coating material will affect the performance of the honeycomb structure absorbing material, so the selection of absorbing coating material is very important. The embodiment of the present application selects a suitable absorbing coating material so that the absorbing material can achieve better absorbing performance at a smaller honeycomb height.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may also be combined, the steps may be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they may still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a microwave absorbing material, characterized in that: The method comprises: Ti3C2T x , carbonyl iron powder, polymer adhesive and organic solvent are mixed to obtain microwave absorbing slurry; Applying the microwave absorbing slurry to the surface of the aramid paper honeycomb; The aramid paper honeycomb coated with the microwave absorbing slurry is dried to obtain a microwave absorbing material with a honeycomb structure.

2. The method according to claim 1, characterized in that The Ti3C2T x The mass ratio of the carbonyl iron powder to the carbonyl iron powder is in the range of (1:3) to (1:1).

3. The method according to claim 2, characterized in that The carbonyl iron powder and the Ti3C2T x The mass ratio of the total mass of the adhesive to the polymer adhesive is 5:

1.

4. The method according to claim 3, characterized in that The polymer adhesive is acrylic resin or polyurethane resin.

5. The method according to claim 1, characterized in that The step of coating the absorbing slurry on the surface of the aramid paper honeycomb comprises: The microwave absorbing slurry is coated on the surface of the aramid paper honeycomb by an impregnation method.

6. The method according to claim 1, characterized in that The polymer adhesive is acrylic resin, and the organic solvent is butanone and cyclohexanone; The Ti3C2T x , carbonyl iron powder, polymer adhesive and organic solvent are mixed to obtain a microwave absorbing slurry, including: Mixing 10 g of acrylic resin, 20 mL of butanone and 80 mL of cyclohexanone to obtain a first mixture; The first mixture was mixed with 1.5 g of carbonyl iron powder and 0.5 g of Ti3C2T x Mix to obtain a microwave absorbing slurry.

7. The method according to claim 1, characterized in that The polymer adhesive is polyurethane resin, and the organic solvent is dimethyl sulfoxide and xylene; The Ti3C2T x , carbonyl iron powder, polymer adhesive and organic solvent are mixed to obtain a microwave absorbing slurry, including: Mixing 10 g of polyurethane resin, 70 mL of dimethyl sulfoxide and 30 mL of xylene to obtain a second mixture; The second mixture, 1.0 g of carbonyl iron powder and 1.0 g of Ti3C2T x Mix to obtain a microwave absorbing slurry.

8. The method according to any one of claims 1 to 7, characterized in that: The absorbing material comprises the aramid paper honeycomb and an absorbing coating arranged on the surface of the aramid paper honeycomb. The absorbing coating is obtained by drying the absorbing slurry. The thickness of the absorbing coating ranges from 1.85 mm to 2.00 mm.

9. A wave absorbing material, characterized in that: The absorbing material is prepared according to the method according to any one of claims 1-8.

10. Use of the absorbing material prepared by the method according to any one of claims 1 to 8 in the field of electromagnetic wave absorption.